Visualization on Twitter Activism Networks and Opinion Leaders: The Case of #FreeWestPapua - Ardiyanti, Handrini; Revianti Sunarwinadi, Ilya; Rusadi, Udi (Jurnal The Messenger, 2022)
Introduction: This study tries to visualize the Twitter activism networks and their opinion leader with the case of #FreeWestPapua activism. This study is important to find out who the opinion leaders and their networks are. This study also provides an overview of how the opinion leader frames opinions about #FreeWestPapua activism on Twitter.Methods: This research used Social Media Network Analysis (SMNA). The SMNA method is the application of the Social Network Analysis (SNA) method to examine conversations on social media. Data collection and data processing are collected and visualised with Netlytic.Findings: The results showed that there are 13 opinion leaders and all of the opinion leaders are from outside Papua. This study concluded that there is alienation in separatist activism in the case of #FreeWestPapua on Twitter. The most influential opinion leader in the separatist activism on Twitter is @VeronicaKoman who has the biggest values and is also active to frame public opinion. #FreeWestpapua activism framed Indonesia as a colonial in diagnostic framing and #FreeWestPapua as a solution in prognostic framing. To attract support from the international community, opinion leaders in #FreeWestPapua activism took advantage of the various #BlackLivesMatter issue and other international moments such as Korindo news by BBC.com.Originality: Although a lot of research on the Free Papua Movement has been done, there has never been a study explains about who opinion leaders and their networks and also how they are framed public opinion about #FreeWestPapua activism on social media.